Optimum dietary protein requirement of a Malaysian freshwater catfish, Mystus nemurus - Khan, M.S.; Ang, K.J.; Ambak, M.A.; Saad, C.R. (Elsevier Science Publishers, 1993)
Six isoenergetic pratical diets ranging from 27% to 50% protein were fed for 12 weeks to triplicate groups of the freshwater catfish Mystus nemurus (25.4±0.89 g body weight and 12.80±0.4 cm total length). The fish were cultured in a recycling water system maintained at ambient environmental temperature. Weight gain was directly proportional to protein levels up to an incorporation rate of 42%; beyond this level no significant growth (P>0.05) either in weight gain or protein gain was observed. Protein efficiency ratio (PER) decreased with increasing protein level. Apparent net protein utilization (ANPU) parabolically increased with increasing dietary protein level but decreased when dietary protein level exceeded 42%. Carcass fat and protein content were negatively correlated while ash content was not affected by varying dietary protein levels. Weight gain, food conversion ratio (FCR), PER and ANPU indicated that a 42% protein diet with digestible protein to energy ratio ( DP E) of 113.82 mg/kcal produced maximum growth under the experimental conditions used.